1986
DOI: 10.1113/jphysiol.1986.sp016089
|View full text |Cite
|
Sign up to set email alerts
|

Innervation and function of hind‐limb muscles in the cat after cross‐union of the tibial and peroneal nerves.

Abstract: SUMMARY1. Peripheral nerves to flexor (common peroneal) and extensor (tibial) nerves in a hind limb of seven 2-6 month old cats were cut and cross-united to study the plasticity in the spinal cord. The extent to which motoneurones from extensor and flexor motor pools were misdirected to their antagonistic muscles was determined by measuring the potentials generated at the spinal roots from the crossed nerves. The axons contributing to the extensor nerves normally leave the cord in the L7 and S1 ventral and dor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…The study showed that the mean difference between the two sides in the innervation contributions of L4 and L5 spinal roots caused by experimental and physiological variability was well within the acceptable limits. Similar findings have also been shown in studies using cats (Buller and Pope, 1977;Gordon et al, 1986). Therefore, we determined the contributions of L4 and L5 spinal roots to the muscles on the contralateral side to obtain a reasonable estimate of extent of partial denervation of the muscles on the experimental side.…”
Section: Discussionsupporting
confidence: 51%
“…The study showed that the mean difference between the two sides in the innervation contributions of L4 and L5 spinal roots caused by experimental and physiological variability was well within the acceptable limits. Similar findings have also been shown in studies using cats (Buller and Pope, 1977;Gordon et al, 1986). Therefore, we determined the contributions of L4 and L5 spinal roots to the muscles on the contralateral side to obtain a reasonable estimate of extent of partial denervation of the muscles on the experimental side.…”
Section: Discussionsupporting
confidence: 51%
“…For example, experiments in newts have shown that transplantations of flexors and exten sors, or the implantation of inverted supernumary limbs do not alter the pattern, even if this pattern is entirely contra productive [7]. Similar experiments with trans plantation of antagonist muscles in cats [8,9] and rats [10,114,115], have confirmed this lack of adaptability of the locomotor pattern. Why is it that the system here seems so rigidly captured in a certain pattern and how is this pattern generated?…”
Section: Evidence For Cpg In Catmentioning
confidence: 99%
“…Thus, although they may be activated in order of increasing size, they may be activated for quite inappropriate movements. In our study an indication of inappropriate muscle function was demonstrated by abnormal movement patterns during locomotion (Gordon et al 1986). In human subjects fine motor control of hand muscles is usually poor following severance and surgical repair of ulnar and median nerves.…”
Section: Discussionmentioning
confidence: 99%
“…activity during locomotion was recorded from the cross-reinnervated and normally innervated hind-limb muscles. The methods and results of these experiments have been reported in the preceding paper (Gordon et al 1986).…”
Section: Methodsmentioning
confidence: 99%